Establishing the Capabilities of the Murchison Widefield Array as a Passive Radar for the Surveillance of Space - Brendan Hennessy; Mark Rutten; Robert Young; Steven Tingay; Ashley Summers; Daniel Gustainis; Brian Crosse; Marcin Sokolowski (Remote Sensing, 2022)
This paper describes the use of the Murchison Widefield Array, a low-frequency radio telescope at a radio-quiet Western Australian site, as a radar receiver forming part of a continent-spanning multistatic radar network for the surveillance of space. This paper details the system geometry employed, the orbit-specific radar signal processing, and the orbit determination algorithms necessary to ensure resident space objects are detected, tracked, and propagated. Finally, the paper includes the results processed after a short collection campaign utilising several FM radio transmitters across the country, up to a maximum baseline distance of over 2500 km. The results demonstrate the Murchison Widefield Array is able to provide widefield and persistent coverage of objects in low Earth orbit.